An Analysis of Students Ability in Implementing Basic Teaching Skills in The Micro Teaching Class at Fkip Unram - Tania Anazmi Anggraini; I Made Sujana; Amrullah Amrullah; Muhamad Amin (Journal of English Education Forum (JEEF), 2026)
This study analyzes the basic teaching skills applied by English Education students at FKIP UNRAM. The subjects of this study were 12 sixth-semester English Education students. A qualitative approach was used in this research. The instruments employed included semi-structured interviews and microteaching video analysis. The researcher used observation sheets to analyze each teaching skill and employed frequency to determine how often each aspect appeared.For the interviews, the researcher used the Zoom application on a laptop to record the interview sessions. The results of the study indicate that the students applied all eight basic teaching skills, with varying levels of proficiency, and the skill most apllied by the students were set-induction, explanation, reinforcement, and stimulus variation. The inhibiting factors identified were divided into two categories: internal factors, which include, nervousness, lack of mastery of teaching skills, lack of self-confident, anxiety, introversion, limited vocabulary/English proficiency, and forget lesson plan. External factors, which include limited time and being observed by others student. Future research is recommended to explore other factors affecting the effectiveness of applying the eight basic teaching skills in the context of microteaching.